A Pesantren-Based Model of Islamic Education for Cultivating Santri Character among University Students - Abdul Muin (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Islamic higher education institutions based on the pesantren system possess distinctive characteristics in integrating academic traditions with pesantren values. This integration serves as an important strategy in producing graduates who are not only intellectually competent but also possess strong religious character and noble morals. The concept of students with a santri spirit has become a relevant identity for Islamic higher education institutions in responding to the challenges of modernity and moral degradation among the younger generation. This study aims to: (1) analyze the model of pesantren-based Islamic education in shaping students with a santri spirit; and (2) examine the implementation of academic and pesantren cultures in students’ daily lives. This study employed a qualitative approach using a case study design at the Institut Agama Islam Kyai Haji Ahmad Syairazi Al-Arsyadi (IAI KHAS Al-Arsyadi), Hulu Sungai Selatan Regency, South Kalimantan. Data were collected through observations of academic and pesantren activities as well as documentation of student development programs. Data analysis was conducted through data reduction, data display, and conclusion drawing, with triangulation techniques employed to ensure data validity. The findings reveal that the pesantren-based educational model is implemented through the integration of academic and pesantren curricula, habituation of worship practices, reinforcement of Islamic manners (adab), and dormitory-based guidance systems. The implementation of this model contributes to the development of students’ religious character, discipline, responsibility, and independence. This study contributes to the development of pesantren-based Islamic higher education models as an effort to cultivate students with a santri spirit in the contemporary era.